UNIFIED CORPORATE GOVERNANCE PRACTICE OF TRADE PARTNERS WITH INDIA: TOWARDS INTERNATIONAL CODE OF BEST PRACTICES - Mohd. Shamim; Zeenat Fatima; Faozi Abduljalil Gazem Almaqtari (Universitas Negeri Malang, 2018)
This paper investigates the uniformity of corporate governance practices towards international code of best practices. The top 5 trading partner countries with India and export network worldwide have been selected, then from each country, 5 companies are selected which are leading in merchandise export. This study is based on secondary data sourced from published annual reports of the listed companies for the financial year from 2015 to 2017. The study employs descriptive statistics and ANOVA to evaluate the uniformity of corporate governance practices namely; some board characteristics, board committees, listing abroad, international segment or branch, and international governance indicators. It has found that there is statistical significance at the level of 5% that companies follow uniform corporate governance practices relating to board characteristics, board committees, listing abroad, having international segment, and international governance indicators except for executive members, risk management committee, corporate governance and grievance committee, total assets and sales of the company. It is recommended that countries and international bodies should encourage companies toward uniformity of corporate governance.Keywords: Corporate Government Practice, Trade Partners, Best PracticeJEL Classification: M00